2017
DOI: 10.1584/jpestics.d17-046
|View full text |Cite
|
Sign up to set email alerts
|

Partial peptides from rice defensin OsAFP1 exhibited antifungal activity against the rice blast pathogen <i>Pyricularia oryzae</i>

Abstract: Rice blast caused by Pyricularia oryzae is one of the most devastating diseases worldwide. This study aimed to investigate the antifungal activity of rice defensin OsAFP1 and its partial peptides against P. oryzae. The partial peptides near the N-and C-terminal regions of OsAFP1 exhibited approximately the same antifungal activity as the entire protein against P. oryzae. These partial peptides have the potential to be used as fungicides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The following defensins of rice Oryza sativa L. were studied in detail: OsDEF7 and OsDEF8 by Tantong et al [ 67 ] and Weerawanich et al [ 93 ]; OsDEF7, named OsAFP1, was further studied by Sagehashi et al [ 94 ] and Ochiai et al [ 95 ], while Cal1, identical to OsDEF7, was analyzed by Luo et al [ 96 ].…”
Section: Defensins Of Grassesmentioning
confidence: 99%
See 3 more Smart Citations
“…The following defensins of rice Oryza sativa L. were studied in detail: OsDEF7 and OsDEF8 by Tantong et al [ 67 ] and Weerawanich et al [ 93 ]; OsDEF7, named OsAFP1, was further studied by Sagehashi et al [ 94 ] and Ochiai et al [ 95 ], while Cal1, identical to OsDEF7, was analyzed by Luo et al [ 96 ].…”
Section: Defensins Of Grassesmentioning
confidence: 99%
“…The inhibitory activity of OsDEF7 named OsAFP1 against the rice blast pathogen Pyricularia oryzae was studied by Sagehashi et al [ 94 ]. The recombinant peptide was expressed in E. coli as a fusion protein with GST.…”
Section: Defensins Of Grassesmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, antifungal activity assays against Candida albicans , the most common pathogenic fungal species that causes candidiasis in humans 20 , revealed that 4 μM DEF7 completely inhibited its proliferation. In a previous study, DEF7 (designated OsAFP1 in subsequent papers) was reported to exhibit antimicrobial activity against rice pathogenic microbes, such as Pyricularia oryzae 21 and Helminthosporium oryzae 22 . Based on this latest knowledge, basic functional analyses of O. sativa OsAFP1 were conducted to assess its potency as a novel antifungal drug.…”
Section: Introductionmentioning
confidence: 99%